Winning and losing rural localities of the post-socialist economic restructuring: case study of Czechia - Hruška, Vladan; Píša, Jan (Hungarian Geographical Bulletin, 2019)
Retreat from socialism at the turn of the 1980s and 1990s conditioned significant social, economic and environmental changes for former socialist countries. Transformation from the centrally planned economy under the authoritative regime to market economy and democratic system re-structured also economies of rural areas. As a result, the conversion to capitalism constructed successful rural localities enjoying growing wealth whereas, on the other hand, other rural localities struggle with high unemployment, low incomes and following emigration of qualified people. This paper, on the example of rural space in Czechia, analyses time spatial development of number of jobs on local level and reveals main factors which have been constructing economically successful and unsuccessful rural localities in the post-socialist period. Based on this, six model responses to post-socialist economic rural restructuring are identified: globally integrated service-oriented, entrepreneurial, industrialised, post-productivist, deindustrialised and post-mining and energy-producing rural localities.